Tapping Performance of Professional and Amateur Darbuka Players - Honda, Kazuaki; Fujii, Shinya (Frontiers in Psychology, 2022)
Motor skills of professional musicians can be regarded as a model to investigate human skill acquisition after prolonged practice. Although rhythmic tapping skills of musicians such as drummers and pianists were investigated previously, tapping performance of hand percussionists are still largely unknown. In this study, we investigated the tapping performance of professional and amateur darbuka players. Three tapping tasks were performed: single-, double-, and triple-finger tapping tasks. The participants were asked to tap as fast as possible for twelve seconds in the single finger tapping task while they tapped as fast and alternate/even as possible in the double- and triple-finger tapping tasks. The tapping speed and variability of inter-tap interval (ITI) and tapping amplitude were assessed for each task. In the single-finger and triple-finger tapping tasks, there was no significant difference in the tapping speed between the professional and amateur darbuka players. In the double-finger tapping task, the tapping speed was significantly faster in the professional players than the amateur players. Interestingly, the professional players showed faster tapping speed in both familiar and unfamiliar patterns of finger coordination. The tapping speed of the double-finger tapping task was significantly correlated with the duration and the age of commencement of darbuka training. The professional players also showed less variability of ITI and tapping amplitude compared to the amateur players. These results suggest that prolonged practice of the hand percussion increases the performance stability and coordination speed of both familiar and unfamiliar patterns.